Assistance for Educators' Scientific Publications Through Writing Scientific Articles for Journal Publications: Pendampingan Publikasi Ilmiah Pendidik Melalui Penulisan Artikel Ilmiah Terbitan Jurnal - Amir MZ, Zubaidah; Zarkasih, Zarkasih; Susilawati, Susilawati; Subhan, Subhan; Hasanuddin, Hasanuddin; Muhandas, Ramon; Vebrianto, Rian; Thahir, Musa (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
One of the activities of professional development for teachers is Scientific Publication. Nonetheless, many teachers have a problem with writing scientific work. Therefore, this community service was done to improve the teachers’ scientific publication through the writing process of a scientific article for journal publication. The type of community service in this research is Participatory Action Research (PAR). The activity of this community service was to provide training/assistance for improving the scientific publication. It was conducted in the form of providing training in article writing for the journal to the teachers in Islamic schools in Teluk Kuantan, especially MAN 1 Teluk Kuantan and it involved 25 teachers. The result of this community service was that the teachers as the training participants had a minimum initial understanding of journal articles and the use in improving learning quality in a class. The average indicator as a whole was only 23.725 and it was categorized as infrequent. All indicators that were questioned were in the ‘infrequent’ category. Meanwhile, based on gender-based motivation, it was found that both genders of the training participant had a motivation that was categorized as ‘frequent’ in participating in the training. However, there was a difference in the aspect for the indicator of being confident to be able to participate well and the readiness of sufficient basic knowledge. The implication of this community service is the importance of this activity and the like for the people to change the mindset and the understanding of the teachers as the training participants to be better.